Repetitive Transcranial Magnetic Stimulation, Cognition, and Multiple Sclerosis: An Overview - Grigorios Nasios; Lambros Messinis; Efthimios Dardiotis; Panagiotis Papathanasopoulos (Behavioural Neurology)
Multiple sclerosis (MS) affects cognition in the majority of patients. A major aspect of the disease is brain volume loss (BVL), present in all phases and types (relapsing and progressive) of the disease and linked to both motor and cognitive disabilities. Due to the lack of effective pharmacological treatments for cognition, cognitive rehabilitation and other nonpharmacological interventions such as repetitive transcranial magnetic stimulation (rTMS) have recently emerged and their potential role in functional connectivity is studied. With recently developed advanced neuroimaging and neurophysiological techniques, changes related to alterations of the brain’s functional connectivity can be detected. In this overview, we focus on the brain’s functional reorganization in MS, theoretical and practical aspects of rTMS utilization in humans, and its potential therapeutic role in treating cognitively impaired MS patients.